Comparative Analysis of Cost of Goods Production Determination Methods at MSME Café Bs Coffeespace - Nur abdi, Muhammad; Burhanuddin, Chairul Iksan; Amran, Amran; Rizal, Samsul (Fakultas Ekonomi Universitas Garut, 2024)
The main objective that requires special attention is the Cost of Goods Manufactured (COGS), especially in the midst of MSME competition in producing quality products but having affordable sales prices. This research aims to compare methods of calculating the cost of goods manufactured that are accurate to ultimately produce the appropriate sales price. The research that has been carried out uses a quantitative descriptive method and a comparative approach to be able to compare the two methods, namely full costing and variable costing. As for the results of the research that has been carried out, making 450 chocovado blend drinks, 400 mint ginger honey drinks and 370 redvelvet signature drinks there is a difference of Rp. 2,139.25 for chocovado blend, Rp. 2,448.5 for mint ginger honey drinks and Rp. 2,602.17 for redvelvet signature. This means that the COGS obtained by the full costing method tends to be high when compared to the variable costing method. The reason is the different treatment of factory overhead costs (BOP). The full costing method includes all variable and fixed cost elements, while the variable costing method includes variable costs only. It is hoped that the company can consider what method or method is suitable for the company, be it the full costing or variable costing method, always looking for and learning about scientific developments in relation to the method of determining COGS so that it is always in line with applicable regulations.